2016
DOI: 10.3402/dfa.v7.29605
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for occurrence and recurrence of diabetic foot ulcers among Iraqi diabetic patients

Abstract: There are a few studies that discuss the medical causes for diabetic foot (DF) ulcerations in Iraq, one of them in Wasit province. The aim of our study was to analyze the medical, therapeutic, and patient risk factors for developing DF ulcerations among diabetic patients in Baghdad, Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
(14 reference statements)
4
9
3
Order By: Relevance
“…The reasons might be the unequal number of patients in the two groups (those developing foot ulcer were 356 as opposed to 1696 who did not develop foot ulcer). This finding was compatible with other studies like Yazdanpanah et al12 a prospective cohort study done in Iran and Mohammed et al6 a cross sectional study done in Iraqi patients. Sample size was low in both these studies as compared to our study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The reasons might be the unequal number of patients in the two groups (those developing foot ulcer were 356 as opposed to 1696 who did not develop foot ulcer). This finding was compatible with other studies like Yazdanpanah et al12 a prospective cohort study done in Iran and Mohammed et al6 a cross sectional study done in Iraqi patients. Sample size was low in both these studies as compared to our study.…”
Section: Discussionsupporting
confidence: 93%
“…Poor compliance and dyslipidemia were found statistically significant risk factors for DFU. However, some studies did not found them associated with diabetic foot ulcer 6. Another finding of this study was predominance of male patients developing DFU.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations